Reciprocal effects between post-migration risk factors for mental health and barriers to access to treatment among refugees and asylum seekers: what have we learnt? - Bartolomei, Javier; Reyre, Aymeric (Frontiers in Psychiatry, 2025)
The last decade has been marked by increasing numbers of forcibly displaced persons around the world, bringing new challenges for Western general and mental health services. For years, research has been focused mainly on pre- and per-migration risk factors for refugees and asylum seekers’ (RAS) mental health. Lately more attention has been given to post-migration risk factors whose impact seem to have been largely underestimated. Uncertain administrative processes, separation from family remaining in the home country, housing conditions, access to professional activity or training and social isolation appear to be associated with a higher prevalence of mental health disorders among RAS. In parallel, the organization of western medical services seem to be maladjusted to RAS’ needs and therefore contributes to post-migration stress factors impact on mental health. Integration of legal advice and job coaching in medical units, planned strategies to decrease social isolation, access to translators and cultural mediation in addition to access to training to local language are insufficiently considered. From our point of view, insufficient attention has been paid to the reciprocal effects between x and y. In order to better tailor healthcare provision to RAS, it seems necessary to take into account the mutual reinforcement of these issues and to develop approaches that are better suited to the complexity of the RAS experience and needs.